Call for papers: SAJHE special issue ’Re-imagining writing retreats for academic staff in higher education’ - Paxton, Moragh; Bozalek, Vivienne; Garraway, James (Critical Studies in Teaching and Learning, 2023)
Call for papers for an upcoming special issue of the South African Journal of Higher Education (SAJHE) in 2016: ’Re-imagining writing retreats for academic staff in higher education’.